Pengaruh Model Discovery Learning dan Media Realia Terhadap Keterampilan Berpikir Kritis Peserta Didik - Susiana Sofiahani Evidawati; Erny Roesminingsih; Titi Chandrawati (EduInovasi: Journal of Basic Educational Studies, 2025)
Critical thinking skills play an important role in preparing students to become problem solvers. Improving critical thinking skills requires learning models and media, namely discovery learning and realia media. Because in discovery learning students are encouraged to learn independently and are actively involved in finding concepts and principles through problem solving. In addition, the combination of realia media allows students to gain direct and real experience in understanding the material. The purpose of this study was to analyze the effect of using the discovery learning model and realia media together on the critical thinking skills of fifth grade students of SD Negeri Gugus 1, Slahung District, Ponorogo. This study used a quantitative method with an ex-post facto research design. The sample in this study was fifth grade students of SD Negeri 1 Senepo and SD Negeri 2 Senepo Ponorogo totaling 33 students. The data collection instrument used a questionnaire and test. The data analysis technique was through the data analysis prerequisite test with the normality test and homogeneity test, and the influence test with the hypothesis test. The results show that the discovery learning model significantly influences students' critical thinking skills, realia media significantly influences students' critical thinking skills, and the discovery learning model and realia media simultaneously significantly influence students' critical thinking skills. If the discovery learning model and realia media increase, then critical thinking skills increase, and vice versa.